Al-Ashil Fi Al Tafsir (Pengertian dan Karakteristik) - Hery Sahputra; Wahyu Ramadhani Rambe; M. Naqsyabandi S; Khoirul Anwar (Jurnal Riset Rumpun Agama dan Filsafat, 2025)
This studyiuses a quantitative method with a descriptive approach to analyze the concept of al-Ashil fi al-Tafsir, both in terms of its definition and characteristics. Al-Asli fi al-Tafsir is a fundamental principle in Qur’anic exegesis that refers to the primary sources in understanding the sacred text, such as theiQur’an itself, the Prophet’s hadith, ijma’ (scholarly consensus), and qiyas (analogical reasoning). This concept serves as a crucial foundation for interpreters to maintain the authenticity of interpretations so they remain aligned with the intended meaning of the revelation. This study gathers data from 15 journals discussing exegesis methodology and fundamental principles in understanding the Qur’an. The findings indicate that *al-Asli fi al-Tafsir* has several key characteristics, including adherence to the text, maintaining the original meaning, and considering the historical context of revelation. Furthermore, this principle emphasizes the importance of deep Arabic language comprehension and the continuity between the text and its practical application in daily life. Thus, this studyiprovides an in-depth insight into the fundamental principles of Qur’anic exegesis.